Karakteristik Anak Balita dengan Kejadian ISPA pada Anak Balita di UPTD Puskesmas Tanjung Agung Kecamatan Baturaja Barat Kabupaten Ogan Komering Ulu Tahun 2018 - yeviza Puspitasari; Yustina Oktarida (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2018)
ISPA is often dubbed "the forgotten killer of children" which is the forgotten killer of children and the highest cause of death of children from other diseases. Incidence of ARI in developing countries with infant mortality rates above 40/1000 live births is 15% - 20% per year The purpose to know the characteristics children factors related to ISPA occurrence in children under five at UPTD Tanjung Agung public health center OKU District in 2018. This method research used an analytical method with a cross-sectional approach. The population of this research is all mothers who bring toddler treatment to MTBS at UPTD Tanjung Agung public health center on Mei - July year 2018 with a sample of 198 respondents. Data analysis used univariate analysis and bivariate analysis using distribution table and Chi-Square statistical test, with a 95% confidence degree. Result of the research: univariate analysis, from 198 respondents got 20.7% responder suffering from a respiratory infection and 79.3% did not suffer from ISPA, 6.6% respondents with BBL at risk and 93.4% respondents with BBL not risk, 16,2% % Of respondents with incomplete primary immunization status and 83.8% of respondents with complete basic immunization status, 84.8% of respondents did not receive exclusive breastfeeding and 15.2% of respondents were exclusively breastfed. Bivariate analysis was obtained in the presence of BBL with ISPA (p-value 0,001), there was a relationship of immunization status with ISPA (p-value 0,001) and there was an exclusive breastfeeding relationship with ISPA (p-value 0,027). Conclusion there is a relationship between birth weight, immunization status, and exclusive breastfeeding with a respiratory infection.